Accumulation of Smooth Muscle 22α Protein Accelerates Senescence of Vascular Smooth Muscle Cells via Stabilization of p53 In Vitro and In Vivo. Issue 10 (October 2017) - Miao, Sui-Bing; Xie, Xiao-Li; Yin, Ya-Juan; Zhao, Li-Li; Zhang, Fan; Shu, Ya-Nan; Chen, Rong; Chen, Peng; Dong, Li-Hua; Lin, Yan-Ling; Lv, Pin; Zhang, Dan-Dan; et al.
Abstract : Objective—: Smooth muscle (SM) 22α, an actin-binding protein, displays an upregulated expression as a marker during cellular senescence. However, the causal relationship between SM22α and senescence is poorly understood. This study aimed to investigate the role of SM22α in angiotensin II (Ang II)–induced senescence of vascular smooth muscle cells (VSMCs). Approach and Results—: We prepared a model of VSMC senescence induced by Ang II and found that the expression of SM22α in VSMCs was increased in response to chronic Ang II treatment. Overexpression of SM22α promoted Ang II–induced VSMC senescence, whereas knockdown of SM22α suppressed this process. Moreover, this effect of SM22α was p53 dependent. Increased SM22α protein obstructed ubiquitination and degradation of p53 and subsequently improved its stability. Furthermore, SM22α inhibited phosphorylation of Mdm2 (mouse double minute 2 homolog), an E3 ubiquitin-protein ligase, accompanied by a decreased interaction between Mdm2 and p53. Using LY294002, a PI3K/Akt inhibitor, we found that PI3K/Akt-mediated Mdm2 phosphorylation and activation was inhibited in senescent or SM22α-overexpressed VSMCs, in parallel with decreased p53 ubiquitination. We further found that SM22α inhibited activation of PI3K/Akt/Mdm2 pathway via strengthening actin cytoskeleton. In the in vivo study, we showed that the disruption of SM22α reduced the increase of blood pressure induced by Ang II, associated with decreased VSMC senescence through a mechanism similar to that in VSMCs in vitro. Conclusions—: In conclusion, these findings suggest that the accumulation of SM22α promotes Ang II–induced senescence via the suppression of Mdm2-mediated ubiquitination and degradation of p53 in VSMCs in vitro and in vivo. Abstract : Supplemental Digital Content is available in the text.